Exploring the interplay of gender, breastfeeding practices, and minimum dietary diversity on stunting among Indonesian children aged 6–23 months - Rossa Amalia; Hartati Eko Wardani; Tika Dwi Tama; Anindya Hapsari (Public Health and Occupational Safety Journal)
Background: Stunting has the highest prevalence compared to other major malnutrition problems. Risk factors for stunting include gender, breastfeeding, and complementary feeding practices. Stunting requires a faster reduction in prevalence to avoid functional losses in children.